Direct in situ observation of toughening mechanisms in nanocomposites of silicon nitride and reduced graphene-oxide. (May 2018) - Ramírez, Cristina; Wang, Qizhong; Belmonte, Manuel; Miranzo, Pilar; Isabel Osendi, M.; Sheldon, Brian W.; Padture, Nitin P.
Abstract: In situ observations are performed, for the first time, of stable crack propagation in nanocomposites of silicon nitride (Si3 N4 ) and reduced graphene-oxide (rGO) inside a scanning-electron microscope. Two different specimen geometries (wedge-splitting and double-cantilever beam) are used to observe crack interactions with rGO stacks in two different orientations (cross-section and in-plane). These observations provide new insights into the unique, effective pull-out of crack-bridging rGO stacks, which appears to be responsible for the extraordinary toughness in the Si3 N4 /rGO nanocomposites. These insights could be used to design and create future ceramic/rGO nanocomposites with superior mechanical properties. Graphical abstract: Unlabelled Image